Percepções dos adolescentes sobre a violência em um assentamento rural - Angela Moreira (2017)
The dissertation aims to investigate the perceptions of adolescents - 10 to 19 years old, in a school located in a Rural Settlement, in the city of Alto Paraíso de Goiás / GO - regarding violence. Therefore, the first part of this paper tries to clarify certain theoretical issues: general aspects about violence; the concept of violence; typology of violence; nature of violence; violence in the world and in Brazil; considerations about adolescence and its relationship with violence. Following the description of the history of the Sem Terra Movement, the research scenario - Sílvio Rodrigues Settlement - is established then the school from this rural settlement is introduced and characterized. This is a cross-sectional survey of a quantitative and qualitative methodological approach about adolescents' perceptions regarding the violence phenomenon. The mixed approach involved the collection and analysis of quantitative and qualitative data. The quantitative component sought to characterize the adolescents sociodemographic profile in violence situation and to build a violence indicator, relating it to school, family, group of adolescents and group of the settlement characteristics. The study population was composed of students from Educandário Humberto de Campos, who took part in the research responding to the Survey on Health and Prevention of Violence - SAUVI. The data of a quantitative nature were stored and tabulated in databases, using the SPSS (Statistical Package for the Social Sciences) Program. Descriptive analysis with frequency distribution, bivariate analysis and multivariate analysis were performed using correspondence analysis. On the collection of qualitative data, it was sought to understand the adolescents perception and significations in relation to violence and the possibilities of coping violence identified by them, through a semi-structured interview. The individuals from the qualitative approach were invited to take part in the study, using non-probabilistic sampling. The systematization and interpretation of the qualitative data of the interviews were carried out through the content analysis defined by Bardin. In regard to the quantitative analysis, it is concluded that epidemiological studies are important to reveal violence in the adolescents reality and help to build interdisciplinary strategies and articulations in overcoming violence, since the way adolescents perceive violence provides important information about the means of overcoming it. And the results of the qualitative analysis made it possible to realize that the adolescents identified several forms of violence in their daily lives. Adolescents perceived violence as a problem present in the settlement carried out by different actors (family members, colleagues and strangers) and in different places, affecting all age groups, occurring in various places, on the street, at school, at home, by various motives, such as racial, sexual and social prejudices. Furthermore, it is concluded that school and family are privileged sources of conflict mediations, allowing a broad action in the field of violence prevention.